Microalgae biomass as an additional ingredient of gluten-free bread: Dough rheology, texture quality and nutritional properties - Khemiri, Sheyma (2021)
Microalgae have been widely used as a source of functional ingredients such as pigments, antioxidants, vitamins, and omega-3 polyunsaturated fatty acids. They also represent a promising alternative source of protein. The objective of this study was to evaluate the impact of the addition of two green microalgae species (Nannochloropsis gaditana L2 and Chlamydomonas sp. EL5) on the techno-functional and nutritional properties of gluten-free bread. Microalgae biomass was added in the amounts of 1.0 and 3.0 g/100 g of flour. The behavior of the dough during the mixing as well as the physicochemical properties of the prepared breads were investigated. Gluten-free bread with N. gaditana L2 and Chlamydomonas sp. EL5 presented significantly higher protein and higher levels of lipids and ash, compared with the control bread. The incorporation of 3% microalgae biomass revealed a 100% increase in iron and calcium contents. The fatty acid profile of supplemented bread changed in a species-specific manner with a particular increase in linolenic acid (18:3 ω3) and a decrease in ω3/ω6 ratio. Besides, due to its original biochemical composition, mainly the highly protein content, microalgae incorporation was found to bring an overall structuring effect on the gluten-free bread texture. However, the dough mixing properties were not affected significantly by microalgae addition. A significant change in color was recorded in doughs, breads, crusts and crumbs. This was caused by the presence of pigment in microalgae biomass, which turned into more intense green-yellow tonalities. A sensory analysis revealed that the supplemented breads scored highest for nearly all the sensory parameters with the 3% N. gaditana L2 bread as the preferred one in terms of global appreciation. This innovative approach gives new insights of the possibility of improving gluten-free products, structurally and nutritionally, using only microalgae as a natural and a sustainable food ingredient